A CO2 optical sensor based on self-assembled metal–organic framework nanoparticles. Issue 27 (20th June 2018) - Chocarro-Ruiz, Blanca; Pérez-Carvajal, Javier; Avci, Civan; Calvo-Lozano, Olalla; Alonso, Maria Isabel; Maspoch, Daniel; Lechuga, Laura M.
Abstract : An optical CO2 sensor is fabricated by integration of a self-assembled, transparent film of zeolitic imidazolate framework-8 (ZIF-8) nanoparticles onto bimodal optical waveguides. This sensor shows a limit of detection (LOD) of 774 ppm CO2, is robust, fast and reusable, and can be stored under humid conditions with no loss in performance. Abstract : The development of devices for sensing and monitoring CO2 levels is crucial for many fields such as food packaging and for human safety indoors. Herein the fabrication of an optical CO2 sensor by integration of a metal–organic framework (MOF) onto bimodal optical waveguides is reported. This sensor is constructed via self-assembly of a transparent film of zeolitic imidazolate framework-8 (ZIF-8) nanoparticles (size: 32 ± 5 nm) on the waveguides. The nanoZIF-8-based sensor exhibits a broad linear response, with limits of detection of 3130 ppm at room temperature and 774 ppm at 278 K. Furthermore, it is robust, selective, fast and reusable, and can be stored under humid conditions with no loss in performance.